2009
DOI: 10.1063/1.3240405
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnet-semiconductor nanowire coaxial heterostructures grown by molecular-beam epitaxy

Abstract: GaAs–MnAs core-shell structures are grown by molecular-beam epitaxy using wurtzite GaAs nanowires on GaAs(111)B. The nanowire structures curve due to the strain at the heterointerface when the substrate is not rotated during the growth, evidencing the diffusion length in the MnAs overgrowth being less than the perimeter of the columns. The MnAs growth is thus demonstrated to take place by direct deposition on the sidewall. The MnAs envelope is m-plane-oriented with the c-axis along the nanowire axis. The magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 19 publications
1
63
0
Order By: Relevance
“…For example, the formation of ferromagnetic precipitates or clusters such as MnAs should be considered as a possible source of magnetism. 11,16,17 Recently, core-shell structured NWs consisting of GaAs/GaMnAs, 18 GaAs/MnAs, 19,20 and InGaAs/GaMnAs 21 have been considered as well. Some of these studies showed that low temperature grown GaMnAs shells can contain high Mn concentrations up to $5% and have ferromagnetic phase transitions above 20 K. 18,21 We have demonstrated previously 11,13 that it is possible to grow GaMnAs NWs by MBE at low temperatures (300-350 C) and if the growth temperature is slightly too high, the formation of MnAs nanoclusters occurs on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the formation of ferromagnetic precipitates or clusters such as MnAs should be considered as a possible source of magnetism. 11,16,17 Recently, core-shell structured NWs consisting of GaAs/GaMnAs, 18 GaAs/MnAs, 19,20 and InGaAs/GaMnAs 21 have been considered as well. Some of these studies showed that low temperature grown GaMnAs shells can contain high Mn concentrations up to $5% and have ferromagnetic phase transitions above 20 K. 18,21 We have demonstrated previously 11,13 that it is possible to grow GaMnAs NWs by MBE at low temperatures (300-350 C) and if the growth temperature is slightly too high, the formation of MnAs nanoclusters occurs on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] To fabricate SFCSNws, commonly first semiconductor Nws are fabricated by epitaxial methods such as molecular beam epitaxy or metal oxide chemical vapor deposition and are in a second growth step coated with the ferromagnetic material. Thereby the magnetic material does not necessarily stick to the Nw shells exclusively.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the insight of ensemble measurements on the Nws themselves that were reported recently by using superconducting quantum interference device magnetometry (SQUID), small angle neutron scattering and ferromagnetic resonance techniques are quite equivocal. [1][2][3][4][5][6][7] Single Nw magnetic investigation on the other hand gives precise information about only the selected structure (one Nw shell) but thus it reflects only the information obtained from one single event of measurement (from one Nw). To draw conclusions from such measurements over all other Nws is hence quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The cylindrical shape of the ferromagnet in such core/shell NWs causes a magnetization along the wire axis, i.e. perpendicular to the substrate surface.…”
Section: Introductionmentioning
confidence: 99%